Application of the Cipp Evaluation Model in Analyzing the Implementation of School of Entrepreneurship Programs in Vocational Schools - Puspita, Chintya Paramita; Purnawirawan, Okta; Sholihah, Muflihatus (Universitas Negeri Semarang, 2019)
Entrepreneurship Learning is expected to be one of the answers for education in Vocational Schools to overcome the problem of the number of unemployed graduates. The lack of entrepreneurs in Indonesia opens up great opportunities for vocational graduates to become entrepreneurs. In line with this, the Directorate of Vocational Education Development (PSMK) pays special attention to strengthening entrepreneurship learning at Vocational Schools by creating a School of Entrepreneurship program. The CIPP (Context Input Product Process) evaluation model is implemented to analyze the level of success of the School of Entrepreneurship program implementation in Vocational Schools that receive this assistance program. The purpose of this study is to analyze the implementation of the School of Entrepreneurship program from the evaluation aspects of context, input, process, and product. The results of the evaluation analysis show that the School of Entrepreneurship program based on the context aspect has a formal foundation, which is Government Regulation No.15 of 2018 (Article 9 B), the input aspect has human resources of students and teachers who have entrepreneurial backgrounds and have good infrastructure, aspect of process of activities is carried out in accordance with a manual that has been determined by the Directorate of Vocational Education Development (PSMK) and is well implemented, product aspects consist of : (1) The formation of the School of Entrepreneurship team; (2) Socialization of the School of Entrepreneurship program in the school environment; (3) Exhibition activities of products of School of Entrepreneurship program; (4) Fostering entrepreneurial activities; (5) Increase in student competence in digital marketing; (6) The creation of independent student entrepreneurial activities; and (7) Evaluation of the continuation of School of Entrepreneurship program.